2021
DOI: 10.1002/clc.23549
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalization deficit of in‐ and outpatient cases with cardiovascular diseases and utilization of cardiological interventions during the COVID‐19 pandemic: Insights from the German‐wide helios hospital network

Abstract: Background Treatment numbers of various cardiovascular diseases were reduced throughout the early phase of the ongoing COVID‐19 pandemic. Aim of this study was to (a) expand previous study periods to examine the long‐term course of hospital admission numbers, (b) provide data for in‐ and outpatient care pathways, and (c) illustrate changes of numbers of cardiovascular procedures. Methods and Results Administrative data of patients with ICD‐10‐encoded primary diagnoses of cardiovascular diseases (heart failure,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
20
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 47 publications
(55 reference statements)
1
20
0
1
Order By: Relevance
“…Single‐centre and nationwide cohort studies showed that COVID‐19 affected referral and hospitalizations of patients with acute HF and that HF was associated with high mortality. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Yet, the impact of COVID‐19 on HF patients and vice versa the relevance of HF events during COVID‐19 in a multicentre international cohort is unknown. 19 , 20 Therefore, the Postgraduate Course in Heart Failure (PCHF) group built an international multicentre registry for hospitalized COVID‐19 patients with CV diseases and/or risk factors (CVDRF).…”
Section: Introductionmentioning
confidence: 99%
“…Single‐centre and nationwide cohort studies showed that COVID‐19 affected referral and hospitalizations of patients with acute HF and that HF was associated with high mortality. 9 , 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 Yet, the impact of COVID‐19 on HF patients and vice versa the relevance of HF events during COVID‐19 in a multicentre international cohort is unknown. 19 , 20 Therefore, the Postgraduate Course in Heart Failure (PCHF) group built an international multicentre registry for hospitalized COVID‐19 patients with CV diseases and/or risk factors (CVDRF).…”
Section: Introductionmentioning
confidence: 99%
“…On March 4, 2020, a supplement to the national pandemic plan regarding COVID-19 was published [ 26 ]. On March 13, 2020, the national pandemic plan has been activated [ 27 ]. In addition, the Kassenärztliche Bundesvereingung (German Association of Statutory Health Insurance Physicians) had published a document regarding influenza pandemic "Risk Management in Medical Practices" in 2008, which is specifically aimed at the outpatient sector [ 28 ].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding outpatient activity, 18 indicators were identified from 8 articles (49,60,62,81,(116)(117)(118)(119). Most of the indicators concerned only to in-person outpatient activity.…”
Section: Outpatient Activity Volumementioning
confidence: 99%